Estimating the potential impact of surveillance test-and-treat posts to reduce malaria in border regions in sub-Saharan Africa: a modelling study - Hillary M. Topazian; Giovanni D. Charles; Nora Schmit; Matteo Pianella; John M. Marshall; Immo Kleinschmidt; Katharina Hauck; Azra C. Ghani (Malaria Journal)
Abstract Background The last malaria cases in near-elimination settings are often found in international border regions due to the presence of hard-to-reach populations, conflict, uneven intervention coverage, and human migration. Test-and-treat border posts are an under-researched form of active case detection used to interrupt transmission chains between countries. Methods An individual-based, mathematical metapopulation model of Plasmodium falciparum was used to estimate the effectiveness of border screening posts on total cases in malaria-endemic sub-Saharan Africa. Results The implementation of international border posts across 401 sub-national administrative units would avert a median of 7173 (IQR 1075 to 23,550) cases per unit over a 10 year period and reduce PfPR2-10 by a median of 0.21% (IQR 0.04 to 0.44%). Conclusions Border posts were most effective in low-transmission settings with high-transmission neighbours. Border posts alone in sub-Saharan Africa will not allow a country to reach elimination, particularly when considering feasibility and acceptability, but could contribute to broader control packages to targeted populations.